Challenges in coronary heart disease prevention – experiences from a long-term follow-up study in Norway. (5th April 2021) - Sverre, E.; Peersen, K.; Perk, J.; Husebye, E.; Gullestad, L.; Dammen, T.; Otterstad, J. E.; Munkhaugen, J.
Abstract: Objective. To determine longitudinal changes in lifestyle behaviour and lipid management in a chronic coronary heart disease (CHD) population. Design. A multi-centre cohort study consecutively included 1127 patients at baseline in 2014–2015, on average 16 months after a CHD event. Data were collected from hospital records, a questionnaire and clinical examination. Seven hundred and seven of 1021 eligible patients participated in a questionnaire-based follow-up in 2019. Data were analysed with univariate statistics. Results. After a mean follow-up of 4.7 years (SD 0.4) from baseline, the percentage of current smokers (15% versus 16%), obesity (23% versus 25%) and clinically significant symptoms of anxiety (21% versus 17%) and depression (13% versus 14%) remained unchanged, whereas the proportion with low physical activity increased from 53% to 58% ( p  < .001). The proportions with reduced physical activity level were similar in patients over and under 70 years of age. Most patients were still taking statins (94% versus 92%) and more patients used high-intensity statin (49% versus 54%, p  < .001) and ezetimibe (5% versus 15%, p  < .001) at follow-up. 73% reported ≥1 primary-care consultation(s) for CHD during the last year while 27% reported no such follow-up. There were more smokers among participants not attending primary-care consultations compared to those attending (19% versus 14%, p  = .026). No differences were found for other risk factors. Conclusions. We found persistent suboptimal risk factor control in coronary outpatients during long-term follow-up. Closer follow-up and intensified risk management including lifestyle and psychological health are needed to improved secondary prevention and outcome of CHD. Trial registration: Registered at ClinicalTrials.gov: NCT02309255. Registered at 5 December 2014, registered retrospectively.